Hemifacial Microsomia - A Case Report & Review of Literature - Dipti Munjal (Wolters Kluwer Medknow Publications, 2006)
HFM was first described in 1861, but it was termed by Pindborg and Corlin in 1964. It represents a heterogenous group of disorders characterized by abnormalities of structures derived from first and second branchial arches. The etiology of this disorder is unknown. The features of this rare disorder are discussed along with a case report.